Analisa Konstruksi Mesin Bubut Duplikat Untuk Profil Kayu Dengan Ukuran Kayu Diameter 15 Cm Dan Panjang 50 Cm - Setiawan, Bambang; Hidayat, Gunawan; Djunaedi, Thomas (Fakultas Teknik UMSU, 2023)
In desaining wood profile lathes, the quality and strength are calculated by analyzing various loads that occur in the lathes and choosing suitable materials to be used in the manufacture of lathes, the materials used are 40 X 40 mm hollow beam type AISI 304 with tensile strength 6 x 108 N / m2, mudulus elasticity 1.9 X 1011 N / m2, performed to calculate the distribution of the load received by the rangkan of 757 N and done to get the results close to the original as a reference for making the lathe frame duplicate the wood profile. To do the simulation, solidwork software is needed as a means to DESAIN and DESAIN the lathe frame strength duplicate the wood profile. Manual calculation results are compared with finite element analysis (FEA) simulations. Strength analysis in the frame is obtained 3.9 X 107 N / mm2, the deflection that occurs is 0.08 mm.